2016
DOI: 10.1038/srep31214
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin stimulates glucagon secretion at high glucose: experiments and mathematical simulations of human A-cells

Abstract: Glucagon is one of the main regulators of blood glucose levels and dysfunctional stimulus secretion coupling in pancreatic A-cells is believed to be an important factor during development of diabetes. However, regulation of glucagon secretion is poorly understood. Recently it has been shown that Na+/glucose co-transporter (SGLT) inhibitors used for the treatment of diabetes increase glucagon levels in man. Here, we show experimentally that the SGLT2 inhibitor dapagliflozin increases glucagon secretion at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 48 publications
(88 reference statements)
5
36
3
Order By: Relevance
“…***p < 0.001 (one-way ANOVA followed by Bonferroni post hoc test). ND, non-diabetic; T2D, type 2 diabetic; NC, no sample control continuation hereof, attenuation of SGLT2 activity by SGLT2 inhibitors was predicted to partly relieve the suppressive actions of glucose on glucagon secretion [23]. However, this model assumes that SGLT2 is expressed by the alpha cell and contrasts to the findings in our study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…***p < 0.001 (one-way ANOVA followed by Bonferroni post hoc test). ND, non-diabetic; T2D, type 2 diabetic; NC, no sample control continuation hereof, attenuation of SGLT2 activity by SGLT2 inhibitors was predicted to partly relieve the suppressive actions of glucose on glucagon secretion [23]. However, this model assumes that SGLT2 is expressed by the alpha cell and contrasts to the findings in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Based on studies performed on human islets or the glucagon-secreting cell line α-TC1, it was suggested that the hyperglucagonaemia might be a direct effect of the inhibitors on the pancreatic alpha cell [5,22], leading to reduced glucose uptake by the alpha cell. Indeed, a mathematical model based on the study by Bonner et al [5] supported the notion that SGLT2 activity in the alpha cell leads to small depolarisations and subsequent inactivation of voltage-gated ion channels, resulting in reduced glucagon secretion [23]. In Expression of glucose transporters in human alpha, beta and delta cells and SGLT2 protein in rat and human islets.…”
Section: Discussionmentioning
confidence: 95%
“…Reduction of S-CPR and serum insulin concentration could be beneficial not only for pancreatic β cell protection but also for preventing cardiovascular events and cancer. Recently, SGLT2I have been reported to increase serum glucagon level [16], but this increase did not occur in the present study, probably because of combination therapy with other anti-diabetic agents. As shown in Table 1, 79.1% of the patients in the present study were being treated with DPP-4I at the baseline and 63.4% with biguanides (metformin).…”
Section: Discussioncontrasting
confidence: 52%
“…26 Accordingly, glucagon-producing alpha cells express SGLT-2 receptors, and dapagliflozin has been shown to increase glucagon secretion when added to isolated human islets. [26][27][28] The present study also shows that there are differences in action between DPP-4 inhibition and SGLT-2 inhibition on beta-cell function, as the prandial AUC for C-peptide was approximately 50% higher after vildagliptin than after dapagliflozin treatment. As glucose levels did not differ between the groups, and as C-peptide kinetics have been shown not to be affected by DPP-4 inhibition 29 or SGLT-2 inhibition, 30 the different actions of the 2 treatments on the Cpeptide response to meal ingestion is compatible with a hypothesis that insulin secretion is augmented more efficiently by DPP-4 Plasma levels of intact and total GIP and GLP-1 before and after ingestion of a mixed meal after 2-week treatment with vildagliptin or dapagliflozin in 28 patients with metformin-treated type 2 diabetes.…”
Section: Adverse Eventssupporting
confidence: 56%
“…The mechanism behind the higher glucagon levels during SGLT‐2 inhibition is less clear, but may be the result of a direct stimulation of glucagon secretion from alpha‐cells, which was first demonstrated in experimental animals in 2002, and is executed by inhibition of cellular glucose entry . Accordingly, glucagon‐producing alpha cells express SGLT‐2 receptors, and dapagliflozin has been shown to increase glucagon secretion when added to isolated human islets …”
Section: Discussionmentioning
confidence: 99%